SGRP annual report 2004/2005: Of the CGIAR System-wide Genetic Resources Programme - CGIAR Systemwide Genetic Resources Programme (2006)
SGRP seeks to improve the effectiveness of the CGIAR System in managing genetic resources as global public goods, including the delivery of research, knowledge and capacity-development. The Programme harnesses the expertise, experience, existing efforts and common areas of interest of centres and their partners, for coherent System-wide action. This report presents an overview of the Programme's activities in 2004/05. These include: an ambitious three-year project to upgrade the facilities and operations of the genebanks of the centres supported by the CGIAR; improvements to SINGER-the System-wide Information Network for Genetic Resources; the development and adoption of a common policy on transgenes; inputs to the development of a Standard Material Transfer Agreement (SMTA) under the International Treaty on Plant Genetic Resources for Food and Agriculture; contributions to establishing a global Platform for Agrobiodiversity Research; and international workshops that helped to advance the centres' thinking with regard to aspects of agricultural biodiversity beyond crops, the first on options and strategies for conserving farm animal genetic resources and the second on methodologies for assessing the value of crop, tree, livestock and aquatic genetic resources.